Maternal co-exposure to polystyrene microplastics and DEHP impairs thyroid function in adult rat offspring - Xin Zhang; Jiangli Li; Zelong Yang; Sida Zheng; Qianhui Huang; Fanyu Meng; Yunbo Zhang (Environmental Pollution, 2026)

Analysis on Spatiotemporal Distribution of Surface Water Quality in the Yangtze River Basin, China - Meiyan Hu; Fanyu Li; Chao Meng; Xiaobin Li; Xiaoxi Chen; Zhen Ni; Shengkai Cao; Xiaodi Zhang; Jingyi Xie; Guangshui Na (Water, Air, & Soil Pollution, 2026)

Correction to: Discovery of core genes and intercellular communication role in osteosarcoma - Fanyu Meng; Xinshe Zhou; Zhi Zhao; Lijia Pei; Weiguo Xia (Journal of Applied Genetics, 2026)

Lactylation: a novel post-translational modification for cGAS-STING pathway - Hongquan Wang; Zhiji Wang; Fanyu Meng; Ying Gao; Ming Zhang; Wei Zhang; Erdan Wang; Kerui Shi; Yuzi Jin (Inflammation Research, 2026)

Low-temperature selective catalytic reduction of NH3 over VPO composited Mn-based catalysts with superior N2 selectivity: Mechanism of inhibiting N2O formation by experiment and DFT - Jin Jiang; Yixuan Teng; Yong Jia; Mingyan Gu; Lina Guo; Fanyu Meng; Jian Yu; Xilou Ding; Shule Zhang; Hongming Long (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat” [Food Packaging and Shelf Life 54 (2026) 101720] - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Vanadium-substituted keggin phosphomolybdic acid catalysts for high efficiency low-temperature NH3-SCR - Yong Jia; Min Hua; Lina Guo; Fanyu Meng; Shule Zhang; Hongming Long (Fuel, 2026)

High-concentration polyethylene and polystyrene microplastics co-exposure shorten insect lifespan and impose ecological risk: Multi-omics evidence from Drosophila melanogaster - Yingyu Liu; Cheng Wang; Caixia Wang; Longhuan Fu; Yunbo Zhang; Zhuo Gao; Zhugen Yang; Fanyu Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Dairy flavor measurements from materials to human perception: Emerging trends and applications - Yangfan Guo; Ying Wang; Haochen Zhou; Xinying Xu; Dongxiao Sun-Waterhouse; Shan Ding; Fanyu Meng; Tao Jiang; Bei Wang (Trends in Food Science & Technology, 2026)

Dynamic reconstruction of Co3O4 through electrochemical activation enhances Co2+ sites for efficient nitrate-to-ammonia electroreduction - Yong Jia; Hang Chen; Yan Fang; Lina Guo; Fanyu Meng; Zhongming Wang; Ruyi Wang (Journal of Environmental Chemical Engineering, 2026)

Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Anti-Colon Cancer Effects of Lysate from Potential Probiotic Yeast Strains Derived from Human Breast Milk - Yi Wu; Chen Li; Zhiyuan Geng; Lihong Wang; Shufeng Wang; Dingxing Zhang; Dongxu Li; Fanyu Meng (Probiotics and Antimicrobial Proteins, 2025)

Applications of biosensing in assessing food flavor: advancements, challenges, and prospects - Kunli Xu; Yangfan Guo; Yadong Wang; Zhijie Yang; Haoying Han; Fanyu Meng; Yanbo Wang; Ruipeng Chen; Bei Wang (Food Chemistry, 2025)

Bioelectrochemical enhancement of waste valorization: synergistic power generation, metal stabilization, and resistome dynamics in electro-stimulated composting system - Tengteng Hu; Haoqi Pan; Yunhan Lin; Jin Yan; Zhuo Gao; Zhugen Yang; Fanyu Meng (Chemical Engineering Journal, 2025)

Organic micropollutants in surface water across China: Occurrence and ecological risk - Rong Cao; Ye Sun; Shuai Sun; Xiaoli Sun; Fanyu Meng; Yueyi Xia; Yuan Gao; Ningbo Geng; Haijun Zhang; Jiping Chen (Water Research, 2025)

Mechanisms for enhanced toluene oxidation performance over YCexMn2-xO5 ternary manganese mullite by B-site substitution - Yijuan Lai; Chuanlai Ling; Fanyu Meng; Yong Jia; Shule Zhang (Fuel, 2025)

Engineering copper single sites in conjugated microporous polymers to enhance selective photocatalytic CO2 methanation - Fanyu Meng; Riyuan Zhang; Haobo Xu; Lifan Shen; Hao Yang; Qinggang Meng; Xingwang Lan (Chemical Engineering Journal, 2025)

Discovery of core genes and intercellular communication role in osteosarcoma - Fanyu Meng; Xinshe Zhou; Zhi Zhao; Lijia Pei; Weiguo Xia (Journal of Applied Genetics, 2025)

Comparative analysis of the volatile flavor compounds of Monascus-fermented cheese with different ripening periods by SPME-GC-MS, SPME-GC×GC-MS, and HS-GC-IMS - Qian Zhang; Yadong Wang; Fanyu Meng; Bei Wang; Yanbo Wang (Food Bioscience, 2024)

Study on ultrasound-assisted extraction of cold brew coffee using physicochemical, flavor, and sensory evaluation - Aolin Yang; Zheting Zhang; Kexin Jiang; Kunli Xu; Fanyu Meng; Weiyan Wu; Zhiqiang Li; Bei Wang (Food Bioscience, 2024)

Multi-Functional hydrogels to promote diabetic wound Healing: A review - Yongyan Yang; Shuangling Zhong; Fanyu Meng; Xuejun Cui (Chemical Engineering Journal, 2024)

Synergistic doping and de-doping of Co3O4 catalyst for effortless formaldehyde oxidation - Wenhao Meng; Xuedan Song; Liurui Bao; Bingbing Chen; Zhen Ma; Jing Zhou; Qike Jiang; Fanyu Wang; Xiao Liu; Chuan Shi; Xingyun Li; Hua Zhang (Chemical Engineering Journal, 2024)

Aging increases the particulate- and leachate-induced toxicity of tire wear particles to microalgae - Min Lv; Fanyu Meng; Mingsan Man; Shuang Lu; Suyu Ren; Xiaoyong Yang; Qiaoning Wang; Lingxin Chen; Jing Ding (Water Research, 2024)

Size distribution and source-specific risks of atmospheric elements in Dalian, a coastal city in north China - Rong Cao; Fanyu Meng; A. Mila; Xiaoli Sun; Haijun Zhang; Jiping Chen; Ningbo Geng (Atmospheric Environment, 2024)

Germplasm evaluation and identification of the population source of hard clam (Mercenaria mercenaria) in China using SSR and COI markers - JunYi Wang; DongXiu Xue; MeiJie Yang; YunLong Ji; Hao Song; Cong Zhou; Pu Shi; YongRen Li; YongJun Guo; FanYu Meng; ChangPing Lai; ShunFeng Cheng; et al. (Frontiers in Marine Science, 2024)
In aquaculture, good germplasm resources are nearly decisive for its development. The hard clam ( Mercenaria mercenaria ), a significant marine aquaculture bivalve in China, has flourished quickly since being introduced from North America in 1997. However, for numerous reasons, it has suffered from germplasm deterioration and uncertain origins. To address these issues, seven microsatellite DNA loci (SSRs) and mtCOI were employed to evaluate germplasm and trace the origins of various Chinese populations. The results of these two molecular genetic markers revealed weak genetic differentiation among all Chinese populations, with high genetic diversity observed across most individuals, except for a few outliers. This suggests an alarming situation regarding germplasm resources in China. Based on results of traceability analysis, the most likely areas of origin for the Chinese populations are Chesapeake Bay and the southern region of Cape Hatteras. This study provides a crucial theoretical foundation for the cultivation, conservation, and subsequent introduction of hard clam populations in China, thereby ensuring the sustainable growth of the hard clam breeding sector.

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

A nationwide investigation on the characteristics and health risk of trace elements in surface water across China - Fanyu Meng; Rong Cao; Xiuhua Zhu; Yuying Zhang; Manxue Liu; Jufang Wang; Jiping Chen; Ningbo Geng (Water Research, 2024)

Synthesis of gel crosslinked composite material from spent cathode carbon blocks and its application in modified asphalt binders - Xinyu Li; Denghui Ren; Shencheng Fan; Zibo Lin; Fanyu Meng; Haisheng Wu; Fang Lai; Jing Li (Journal of Cleaner Production, 2024)

Elucidating the effect of different processing methods on the sensory quality of chestnuts based on multi-scale molecular sensory science - Kunli Xu; Zheting Zhang; Kexin Jiang; Aolin Yang; Tielong Wang; Lingyun Xu; Xiaodong Li; Xiaoli Zhang; Fanyu Meng; Bei Wang (Food Chemistry, 2024)

Efficient activation of peroxymonosulfate by Z-scheme NiCo2O4/BiVO4 heterojunctions for rapid degradation of tetracycline under visible light irradiation - Hao Chen; Fanyu Meng; Shuang Li; Tengfeng Xie; Dejun Wang; Yanhong Lin (Journal of Water Process Engineering, 2023)

New insight into vanadium phosphorus oxides (VPO/TiO2) catalysts for NO removal with NH3-SCR at low temperature: Relationship between non-VO phases and SO2&H2O resistance - Jin Jiang; Lina Guo; Jing Yuan; Fanyu Meng; Zhongming Wang; Fuping Qian; Shule Zhang; Yiqing Zeng; Yong Jia; Mingyan Gu (Fuel, 2023)

Based on HS-SPME-GC-MS combined with GC-O-MS to analyze the changes of aroma compounds in the aging process of Citri Reticulatae Pericarpium - Kexin Jiang; Kunli Xu; Jiao Wang; Fanyu Meng; Bei Wang (Food Bioscience, 2023)

Synergistic effect of F and triggered oxygen vacancies over F-TiO2 on enhancing NO ozonation - Lina Guo; Xu Zhang; Fanyu Meng; Jing Yuan; Yiqing Zeng; Chenyang Han; Yong Jia; Mingyan Gu; Shule Zhang; Qin Zhong (Journal of Environmental Sciences, 2023)

Enhancement of low temperature NH3-SCR activity and SO2 & H2O tolerance over VPO-Co/TiO2: Determining roles of acidity via Co doping - Guang Chen; Jie Yu; Bing Liu; Nana Shao; Jing Yuan; Fanyu Meng; Shihua Zhang; Yihua Chen; Lina Guo (Journal of Environmental Chemical Engineering, 2023)

Comprehensively evaluating and modelling droplet diameters and kinetic energies of low‐pressure sprinklers - Xin Hui; Yudong Zheng; Fanyu Meng; Haibin Tan; Haijun Yan (Irrigation and Drainage, 2022)
Proper droplet diameter and kinetic energy can effectively reduce the risk of soil erosion during low‐pressure sprinkler irrigation. In this study, we comprehensively evaluated the radial distributions of droplet diameter, velocity, kinetic energy, kinetic energy per unit droplet volume, and specific power for three common low‐pressure sprinklers, i.e. Nelson D3000, R3000 and Komet KPT, with two operating pressures (103 and 138 kPa) and three nozzle outlet diameters (3.97, 5.95 and 7.94 mm). Additionally, the relationships between these droplet characteristic parameters were analysed. Overall, the maximum values of five characteristic parameters were observed at the end of the jet under various treatments. Although R3000 had a larger droplet diameter (0.10–6.42 mm) and kinetic energy (1.08 × 10 −10 –8.59 × 10 −3 J) distribution range than D3000 and KPT, the D3000 specific power (mean value of 0.4274 W m −2 ) was the highest of the three sprinklers. Therefore, KPT was suggested more in low‐pressure sprinkler irrigation than in the other two sprinklers because its application rates were reduced along the radial direction. In addition to selecting a suitable sprinkler type for minimizing specific power, determining a reasonable sprinkler spacing was also significant ( P −2 , NRMSE = 29%) was proposed. This study provides a key basis for the selection and combination of low‐pressure sprinklers.

Sorption and transport of Mn2+ in soil amended with alkali-modified pomelo biochar - Qiang An; Sheng Zhu; Zheng Li; Shuman Deng; Bin Zhao; Fanyu Meng; Ningjie Jin; Xiaozhou Ren (Environmental Science and Pollution Research, 2021)

Bioelectricity generation and dewatered sludge degradation in microbial capacitive desalination cell - Fanyu Meng; Qingliang Zhao; Xiaolin Na; Zhen Zheng; Junqiu Jiang; Liangliang Wei; Jun Zhang (Environmental Science and Pollution Research, 2017)